SERUM ALDOSTERONE LEVEL DYNAMICS AND CARDIAC REMODELING IN MYOCARDIAL INFARCTION PATIENTS WITH UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA TREATED WITH SELECTIVE ALDOSTERONE RECEPTOR BLOCKER - E. P. Miroshnichenko; N. Y. Dranenko; I. Y. Goryanskaya; A. A. Gagarina; A. V. Ushakov (Евразийский Кардиологический Журнал, 2018)
Aim. To study serum aldosterone level dynamics and cardiac remodeling characteristics in myocardial infarction (MI) patients with undifferentiated connective tissue dysplasia (UCTD) treated with selective aldosterone receptors antagonist eplerenone.Study population and methods. A total of 110 MI patients with and without UCTD and 32 healthy controls without cardiovascular pathology and without signs of UCTD were enrolled in the study. Clinical examination, phenotyping, echocardiography and serum aldosterone levels evaluation were performed. MI patients were divided into 3 groups: I (n=20) - patients with UCTD who was treated by eplerenone additionally to basic therapy of MI; II (n=60) - patients without UCTD treated by basic therapy of MI; III (n=30) -patients with UCTD treated by basic therapy of MI only.Results. All MI patients regardless of UCTD presence had increased serum aldosterone in the first day of MI. In 28 days the significant increase of serum aldosterone level in group I in comparison with groups II, III and control group was observed. Analysis of structural and functional characteristics of the heart in MI patients in a 6 month after MI had shown more significant left ventricle enlargement and decrease of cardiac pump function in group III compared to group I.Conclusion. Presence of UCTD in MI patients does not affect serum aldosterone levels dynamics. Inclusion of eplerenone in the treatment of MI patients with UCTD during 6 months inhibits left ventricular dilatation and attenuates reduction of its ejection fraction.